SCIENCE LITERACY OF BULGARIAN STUDENTS THROUGH TEACHERS' VIEW - S. Todorova (Trakia Journal of Sciences)
The article presents results and analysis of data from a national survey conducted among teachers, regarding the science literacy of Bulgarian students. The conducted international studies PISSA and TIMSS show that the results of Bulgarian students are below the average for the study. In the field of natural sciences, the most significant decrease was observed, with the average score of Bulgarian students according to PISSA data falling by 22 points in the study conducted in 2018, compared to 2015. The research presented in this article was conducted through an online questionnaire with 15 questions of different types. 105 teachers participated in the study. The results show that teachers use different methods to build science literacy in students. Teachers share that they are partially or not familiar with the results of the PISSA and TIMSS international studies conducted in our country, in the years 2015 and 2019. They need additional methodical help and literature for acquiring further knowledge and skills for improving science literacy among students.